The role of long non‐coding RNAs in lung cancer metastasis: Molecular mechanisms, pathogenesis and clinical implications - Musaffe Tuna; Gordon B Mills; Christopher I. Amos (Clinical and Translational Medicine)
Abstract Lung cancer remains the leading cause of cancer‐related death in both women and men in the United States and globally. Even among early‐stage patients who undergo surgical resection, a significant portion of patients develop metastases. Notably, approximately 30% of patients with stage I lung cancer experience relapse. For decades, protein‐coding genes dominated cancer research, driven by the belief that these genes were the primary contributors to tumorigenesis. Despite advances in treatment our understanding of fundamental mechanismsdriving lung cancer progression remains limited. The overall 5‐year survival rate for all stages of lung cancer combined is approximately 20%. Surgical resection remains the best option for early‐stage diseases, whereas chemotherapy, immunotherapy or combination therapies are primarily employed in advanced stages. Frequent treatment failure due to therapy resistance, highlight the urgent need to identify novel biomarkers for early diagnosis, prognosis, and the development of more effective therapies. This underscores the necessity and urgency of researching lncRNAs. The advent of next‐generation sequencing and other high‐throughput technologies guided the discovery of a new class of molecules, non‐coding RNAs (ncRNAs) that play a role in many aspects of cellular physiology. Among the various types of ncRNAs, long non‐coding RNAs (lncRNAs)—which have transcripts longer than 200 nucleotides—have emerged as key regulatory molecules in a myriad of cell functions by interacting with DNA, with other RNAs, including mRNA, miRNA and with proteins. Importantly, lncRNAs play crucial roles in cancer progression, including metastasis by activating oncogenic pathways, promoting epithelial‐mesenchymal transition, remodelling the extracellular matrix, and inducing angiogenesis. Notably, they can function as both oncogenes and tumour suppressors. MALAT1 is one of the lncRNAs that contribute to metastasis and resistance to tyrosine kinase inhibitors in lung cancer. This review summarizes the role of lncRNAs in cancer, with a specific emphasis on their contributions to lung cancer metastasis. Key points LncRNAs are significant players in lung cancer metastasis. LncRNAs can be used as therapeutic target in lung cancer. LncRNAs can be used as prognostic factors in lung cancer. Exosomal lncRNAs can be used to predict prognosis in lung cancer.